Plant composition and arrangement of agroforestry systems in oil palm smallholdings - Mohd Salleh, Anizah; Harun, Nor Zalina; Mansor, Mazlina (IIUM Press, 2017)
Malaysia is known as the largest exporter and second largest producer of world palm oil market. Despite such contributions, a huge amount of forest land has been supplanted by oil palm cultivation. This activity is considered as a major driver of deforestation, which contributes to three-quarters of tropical deforestation globally. The critique of this field reveals agroforestry systems as an option to overcome the issues brought up by a monoculture system of oil palm cultivation. This inquiry is directed to study plant composition and arrangement for agroforestry systems in oil palm smallholdings. To this end, three objectives formulated which are: (i) to investigate agroforestry systems as sustainable agriculture practices in oil palm smallholdings, (ii) to explore plant composition and arrangement of agroforestry systems for a sustainable oil palm smallholdings, and (iii) to recommend sustainable plant composition and arrangement of agroforestry systems that can be implemented in oil palm smallholdings. Data were gathered using a qualitative approach involving 10 oil palm smallholdings at Kluang, Johor. Three methods of data collection were adopted, which consists of non-participant observation, semi-structured interview, and document analysis. The collected data were analyzed using thematic analysis that were triangulated to provide systematic, efficient, and accurate data analysis. The findings suggested that there are 50 plant species and 3 types of arrangement suitable to be implemented in oil palm smallholdings. The plant species are in the ranged of perennial crops, annual crops, leguminous cover crops, and grasses. Meanwhile, the arrangement involves triangular, double avenue, and boundary planting systems. Further analysis traced that these plant species and arrangement can be categorized into two main categories which are: (i) sustainable plant composition and arrangement, and (ii) unsustainable into sustainable plant composition and arrangement.